Organization Processes Supported by Business Intelligence System - Remigiusz TUNOWSKI (Communications of International Proceedings, 2021)
This study will establish a baseline for further research on the subject area. The main research problem presented in the paper is, in essence, the answer to the question whether and what processes in the organization can be influenced by Business Intelligence (BI) systems. As part of the search for a solution to the undertaken research problem, processes in organizations were analyzed in terms of being supported by a BI class system. The assessment of the potential impact on particular processes was documented by discussing possible analyses, which might be successfully performed by the Business Intelligence system. As a result, the list of potential processes in the organization was collected. The list of analysed processes will be useful for further research in the area of the impact of Business Intelligence systems on processes in organizations. An additional effect of this publication is the fact that the research implications of this study may suggest to the top management that the implementation of Business Intelligence systems can bring tangible benefits to organizations by identifying those specific processes in the organization that can be improved.
Keywords: business intelligence; processes in the organization; the impact of business intelligence on organizations